CONSUMERS INCLINATION TOWARDS ELECTRIC VECHILES (EV) - Lakshmi, Dr.S.; Kumar, Dr.J. (The journal of contemporary issues in business and government, 2022)
Ten years before Electric vehicles (EVs) are a dreaming one for the public and now it is implemented practically for achieving a sustainable development in transport sector in the future, due to the high fuel price and to control the carbon emissions, low noise, high efficiency, and flexibility in grid operation and integration. Electric Vehicles (EV), as a way to decrease the greenhouse effect, In this study we clearly explained about how the consumers are inclinated towards electric vehicle. Since the day of covid, people think about personal vehicles and there has been a gradual movement towards EV and hybrid vehicles. Instead of seeking for discounts as the demand for EV continues to rise in the recent days mainly it helps to save money.